Panchkarma in Surgical Diseases: A Review of Classical Text: Life Sciences-Ayurvedha - Kumar, Dr. Akshay; Dasar, Dr. Devyani; Sharma, Dr. Pariksha (International Journal of Life Science and Pharma Research, 2023)
Panchkarma is a part of Kayachikitsa with a fivefold cleansing or detoxification process, which includes Vamana, Virechana, Basti, Raktamokshana, and Nasya. These fivefold Shodhana karmas exert their efficacy by influencing different doshas or adhisthana and expelling them through the nearest exit source. Although the field of Panchkarma comes under Kayachikitsa, there are several mentions of the extensive use of Panchkarma in all branches of Ashtanga Ayurveda. For example, Shalya tantra is one of the crucial branches of Ashtanga Ayurveda which specifically focuses on the process of Shalya (foreign body) extraction. In contrast, Acharaya Sushruta mentions using Panchkarma as purva karma for different surgical processes. Like any other Nidana (etiological factor), Shalya also acts as a nidana by vitiating doshas according to its location, nature or kala (period). The study’s primary aim is to do a comprehensive review of Panchkarma procedures mentioned in surgical diseases covering all references and studies. Research is conducted by searching various classical texts and databases to fulfil the objective. Along with its application in surgical diseases, this article also highlights the application of Panchkarma in emergency conditions. In this article, all Panchkarma processes mentioned in surgical diseases are explained, and a table is made for reviewing it easily. Thus, this review will focus on the Panchkarma process mentioned in Shalya Tantra and the need for extensive research in this field, as most procedures still need to be explored.